Positional accuracy validation of digital orthophoto mapping: case Bahir Dar - Vermeer, Martin; Getahun, Zinabu; Bedada, Tulu Besha; Gessesse, Berhan (Nordic Journal of Surveying and Real Estate Research, 2018)
This study used in-situ Global Positioning System (GPS) measurements to assess the accuracy of horizontal coordinates of the orthophoto map for Bahir Dar city. The GPS data was least-squares adjusted using the GAMIT/GLOBK and Leica GeoOffice (LGO) software packages. Local and regional GPS reference stations, including the continuously operating reference station of Bahir Dar University’s Institute of Land Administration, were included in the adjustment. Thus, horizontal coordinates at five checkpoints were obtained, which were used to assess the horizontal positional accuracy of these same points in the orthophoto map. Point accuracies found for point locations read from the orthophoto map were inferred to be on the level ±0.15 m. This meets well the requirement of the Ethiopian Mapping Authority of ±0.30 m for maps on scale 1 : 2000, which are sufficient for cadastral and land-use planning use everywhere, also in urban areas, though not perhaps in dense city centres.